2019
DOI: 10.3390/coatings9080481
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silphenylene-Containing Siloxane Resins Exhibiting Strong Hydrophobicity and High Water Vapor Barriers

Abstract: The novel phenylenedisilane, 1,4-bis(dimethoxyphenylsilyl)benzene (BDMPD), was successfully synthesized via the reaction between trimethoxyphenylsilane (TMPS) and a Grignard reagent originating from 1,4-dibromobenzene. In comparison to common Grignard reactions, this process was a facile one-pot method. 1H NMR spectroscopy, FT-IR measurements, and elemental analysis confirmed the predicted structure of BDMPD. In addition, vinyl-terminated polysiloxanes containing silphenylene units (VPSSP), which were hydrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Phenyl groups in the main chain and in the pendant chain of polysiloxane endow various special properties, such as thermal stability and water vapor barrier property [1]. Besides, phenyl groups with high molar refraction enhance the refractive index of polysiloxane.…”
Section: Introductionmentioning
confidence: 99%
“…Phenyl groups in the main chain and in the pendant chain of polysiloxane endow various special properties, such as thermal stability and water vapor barrier property [1]. Besides, phenyl groups with high molar refraction enhance the refractive index of polysiloxane.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been proposed to improve the moisture barrier properties of polymers in the packaging field [9][10][11][12], although few related studies have been reported in the field of high voltage insulation. For example, siloxane resins containing VPSSP (vinyl-terminated polysiloxanes containing silphenylene units)-based silphenylene units are found to have superior moisture barrier properties [9]. The incorporation of graphene oxide into silicone adhesive can improve moisture barrier properties as well as other properties desired for the application as a die-attach to light-emitting diodes [10].…”
Section: Introductionmentioning
confidence: 99%